2002
DOI: 10.1103/physrevstab.5.121001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of theory with experiment for positron production from high-energy electrons moving along crystal axes

Abstract: Using the approach developed earlier for the description of the electron-photon showers in axially aligned single crystals, some characteristics of the positron yield measured in recent experiments are calculated. Theoretical estimations display a rather good agreement with experimental results obtained using 3 to 10 GeV electrons aligned to the h111i axis of the tungsten crystals. Such comparison verified that the accuracy of our approach is quite sufficient to make a reliable choice for optimal parameters of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In both cases, the incident electron beam of different energies, up to 10 GeV, was aligned with the < 111 >-axis of a tungsten crystal, which sometimes served as a crystal part of the compound target containing an additional amorphous tungsten part. Basing on the approach developed in [4] and [5], theoretical estimations were obtained in [11], which display a rather good agreement with the experimental results of [10], where only the positrons outgoing in the forward direction (i.e., with a vanishing transverse momentum) were registered for a discrete set of their longitudinal momentum values. However, to obtain a full description of the crystal-assisted positron source, the positron distribution in the whole momentum space, longitudinal and transverse, should be measured.…”
Section: Introductionsupporting
confidence: 63%
“…In both cases, the incident electron beam of different energies, up to 10 GeV, was aligned with the < 111 >-axis of a tungsten crystal, which sometimes served as a crystal part of the compound target containing an additional amorphous tungsten part. Basing on the approach developed in [4] and [5], theoretical estimations were obtained in [11], which display a rather good agreement with the experimental results of [10], where only the positrons outgoing in the forward direction (i.e., with a vanishing transverse momentum) were registered for a discrete set of their longitudinal momentum values. However, to obtain a full description of the crystal-assisted positron source, the positron distribution in the whole momentum space, longitudinal and transverse, should be measured.…”
Section: Introductionsupporting
confidence: 63%
“…Intensive theoretical investigations [3][4][5][6] have indicated that the optimum thickness is less for the crystal target and that the energy deposition in the crystal target is considerably reduced compared with that of a conventional target. Also, they have shown that the crystal effect is much larger at higher incident electron energies.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive theoretical investigations [2,3] have indicated that the optimum thickness is less for the crystal target and that the energy deposition in the crystal target is considerably reduced compared with that of a conventional target. Also, they have shown that the crystal effect is much larger at higher incident electron energies.…”
Section: Introductionmentioning
confidence: 99%